2021
DOI: 10.3390/ijerph18179278
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Detoxification of Some Insecticides in Aqueous Media Using TiO2 Nanocatalyst

Abstract: The present study was performed to fabricate a titanium dioxide (TiO2) nanocatalyst with proper characteristics for the removal of some insecticides (dimethoate and methomyl) from aqueous media. A TiO2 catalyst of regular (TiO2—commercial—/H2O2/UV) or nano (TiO2—synthesized—/H2O2/UV) size was employed as an advanced oxidation process by combining it with H2O2 under light. Moreover, the total detoxification of insecticides after treatment with the most effective system (TiO2(s)/H2O2/UV) was also investigated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The liver is the primary organ concerned with the biotransformation of chemicals, which mostly results in markedly detrimental effects on the biochemistry of hepatocytes, such as excessive ROS generation, which causes oxidative damage not only in the liver but also in other organs, including the kidneys, spleen, and hematopoietic system (36,(43)(44)(45)(46)(47)(48)(49)(50). In this study, Bz-treated rats revealed significant increases in serum bioactivities of AST, ALT, ALP, and LDH and decreased serum total protein, albumin, and α2-and γ-globulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The liver is the primary organ concerned with the biotransformation of chemicals, which mostly results in markedly detrimental effects on the biochemistry of hepatocytes, such as excessive ROS generation, which causes oxidative damage not only in the liver but also in other organs, including the kidneys, spleen, and hematopoietic system (36,(43)(44)(45)(46)(47)(48)(49)(50). In this study, Bz-treated rats revealed significant increases in serum bioactivities of AST, ALT, ALP, and LDH and decreased serum total protein, albumin, and α2-and γ-globulin concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Advanced oxidation processes, especially those with nanocatalysts (Massoud et al, 2021), are promising remediation technologies for removing dimethoate or methomyl from water resources and are suitable for highly contaminated water, such as drainage or wastewater, due to the faster degradation rate via its great degradation power relative to bioremediation, which takes a long time, requires special environmental conditions, and is limited to biodegradable compounds (Derbalah et al, 2014). Although nanomaterials present seemingly limitless possibilities, they bring new challenges to understanding, predicting, and managing potential safety and health risks to workers.…”
Section: Photocatalytic Degradation Of Dimethoatementioning
confidence: 99%
“…Extensive research has been conducted aiming at the development of optimized homogeneous and heterogeneous photocatalytic approaches for the decomposition and detoxification of hazardous organic substances in aqueous solutions, such as antibiotics [ 13 , 15 , 16 , 17 ], pesticides [ 18 , 19 , 20 ] and dyes [ 21 , 22 , 23 , 24 ]. Similar studies have been conducted for the evaluation of the photocatalytic inactivation of microorganisms in suspension [ 25 ], focusing on endospores, considered to be one of the most resistant targets [ 12 , 26 , 27 ], viruses [ 28 , 29 , 30 ], fungi [ 14 ], Gram-positive and Gram-negative bacteria [ 31 ].…”
Section: Introductionmentioning
confidence: 99%